Do You Feel Rushing in the Morning Travel? the Evidence of Daily Travel Pattern Activity During Irregular Traffic Conditions in Post Covid-19, Case Study South Bali Indonesia - I Made Sukmayasa; Efendhi Prih Raharjo; Aris Budi Sulistyo; Putu Diva Ariestaha Sadri; Octaviani Ariyanti (GLOBAL HEALTH SCIENCE GROUP, 2022)
Congestion during rush hours has always been a significant problem for the government, impacting travel time, vehicle operations and air pollution, and health problems. The government has proposed some policies through traffic engineering management and other management applications with the latest technology to overcome such issues. Research related to travel patterns during peak hours is beneficial, which will impact road users' decision-making, particularly during these days when everyone's activities are starting again after COVID-19 restrictions. In this paper, data processing (from Google Maps Distance Matrix API, Typical Google Maps, and Community Mobility Reports) was carried out for almost one month to obtain data on speed and travel time. These data are gathered from four pairs of locations with specific origin/destination of travel patterns in the southern Bali region. The community's travel pattern can be explained based on the one-way ANOVA with Bonferroni and the Kruskal Wallis Test. This paper found that people are in a hurried movement in the morning compared to other busy times, marked by the differences in speed and travel time in the morning commute to afternoon and evening commute during rush hours. This condition illustrates the irregular traffic flow after the Covid-19 restriction rules; thus, drivers can still choose the desired speed to travel. The irregular traffic flow can be seen on community mobility data and typical green traffic during peak hours. This result is significant because of the importance of traffic management during peak hours to optimize the level of road service.